Innovations in managing the agriculture, energy and groundwater nexus: evidence from two states in India. - Mukherji, Aditi (Stockholm International Water Institute, 2012)
This study was conducted in two Indian states of Punjab (in the north) and Karnataka (in the south). An analysis of long term trends in groundwater development and agricultural growth in Karnataka shows two things. First, the growth in irrigation was largely contributed by expansion of groundwater irrigation. Second, with the groundwater development, the state experienced a quantum jump in electricity supply to agriculture. In 1981, electric tubewells were de-metered and a flat tariff regime was introduced. This led to rapid increase in tubewell connections. Electricity was made free in 1998, further perpetuating this crisis. This in turn brought its own share of problems such as difficulty in accounting for agricultural electricity consumption mounting losses of electricity utilities and deterioration of quality of supply to farmers over the years. The Karnataka Electricity Regulatory Commission was formed in 2000 and since then it has urged the electricity distribution companies to improve their agricultural energy consumption estimates, but their methodologies remain as fraught with problems as before with the result that agricultural electricity consumption is likely to be grossly over-estimated as are the number of electric pump sets in the state. The farmers in turn esort to illegal connections and under-reporting of their pump capacity making it even more difficult to arrive at independent estimates of agricultural power consumption. Overall, there is anarchy below the feeder level an anarchy that leaves farmers, utilities and the state government much worse off than they need be. A collateral damage of this anarchy is the deep level of mistrust between the farmers and the utility staff. An analysis of groundwater development and agricultural growth in Punjab shows two important trends. First, growth in irrigation extent and irrigation intensity was largely contributed by expansion of groundwater irrigation. Second, with the groundwater development, the state experienced crop specialization to bi-crop rotation of rice-wheat which further increased the demand of groundwater. Since the increase in groundwater irrigation was made possible with tube-well energization, Punjab's agriculture got highly dependent on electricity supply. This in turn brought its own share of problems such as difficulty in accounting for agricultural electricity consumption in the absence of metering, mounting losses of state utility due to non-payment of subsidy amount by the government and deterioration of quality of supply to farmers over the years.